Die filioque: Ekumeniese speelbal of reformatories teologiese noodsaaklikheid - Otto, J. (Hervormde teologiese studies, 1994)
The filioque The current debate within the ecumenical movement about the filioque has its origin in the Greek Orthodox church’s demand that the Nicenco- Constantinopolitanum be accepted in its original form. Only if a universally acceptable symbol is found, can there be any hope of progress in the movement to unity. The choice put by the ecumenical movement is between unity and filioque. It is the contention in this article that this choice is a false one. From an overview of the most important historical aspects of the problem, the reader is confronted by the problem. This is followed by a discussion of the points of view of the orthodox church, the ecumenical movement and Protestant theology. This discussion shows the impasse which the choice between fdioque and unity creates. A discussion of the concept of models, as instrument within theological language, has as goal to show that this impasse can be solved. I f theological language uses models in its discussions, any talk about filioque will be open to more than one interpretation. Filioque can still be used to say something about the Trinity, even in the ecumenical movement.